PENGARUH MASSAGE PUNGGUNG TERHADAP PENURUNAN NYERI PADA IBU POST SECTIO CAESAREA - Sri Wulan; Riris Sitorus (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2018)
Sectio caesarea contain the biggest risk, the operation of feel the pain to effect of slice post operate for and most was often experienced of by that was natural by back ache and fatigue of mother post operate for the sesarea and to overcome the pain in bone or feel the pain cause can be conducted by masase back representing method elektif in treatment function that was for the prepare of pasca operastif, especially at patient post operate for the Sectio caesarea. This research to analyse the Influence of Masase Back To Degradation of Quality Of Pain In Bone at the Mother Post Operate for the Sectio caesarea in Hospital GrandMed of Lubuk Pakam Deli Serdang. This Research Type have the character of qualitative use the method of quasi eksperimental without group control with the approach of One Group Pretest - Postest Desaign. Popolasi amount to 30 responder, Sampel Research amount to 10 responder by using technique of purposive sampling. Analyse the data use the test t-test with the trust level 95 (α= 0,05). Pursuant to analysis of there was relation of which signifikan of among influence of masase back to degradation of was quality of pain in bone of at the patient post operate for the Sectio caesarea. Before done by masase 10 responder experience of the pain was and after done by masase 8 responder of pain in bone was and 2 light pain in bone responder. Using test of paired t test by p value α= 5% p (0,001< 0,05. There before researcher to mothers or Family experience post Sectio caesarea can be aplicatied to back masase to deficience back pain.